A systematic review of the effectiveness of employer‐led interventions for drug misuse - Akanbi, Maxwell O. (J Occup Health, 2020)
AIMS: Employers in the United States incur substantial costs associated with substance use disorders. Our goal was to examine the effectiveness of employer‐led interventions to reduce the adverse effects of drug misuse in the workplace. METHODS: We conducted a systematic review of studies that evaluated the effectiveness of recommended workplace interventions for opioids and related drugs: employee education, drug testing, employee assistance programs, supervisor training, written workplace drug‐free policy, and restructuring employee health benefit plans. We searched PubMed MEDLINE, EMBASE (embase.com), PsycINFO (Ebsco), ABI Inform Global, Business Source Premier, EconLit, CENTRAL, Web of Science (Thomson Reuters), Scopus (Elsevier), Proquest Dissertations, and Epistemonikos from inception through May 8, 2019, with no date or language restrictions. We included randomized controlled trials, quasi‐experimental studies, and cross‐sectional studies with no language or date restrictions. The Downs and Black questionnaire was used to assess the quality of included studies. The results were reported using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. RESULTS: In all, 27 studies met our inclusion criteria and were included in the systematic review. Results were mixed, with each intervention shown to be effective in at least one study, but none showing effectiveness in over 50% of studies. Studies examining the impact of interventions on workplace injuries or accidents were more commonly reported to be effective. Although four studies were randomized controlled trials, the quality of all included studies was “fair” or “poor.” CONCLUSIONS: Despite the opioid epidemic, high‐quality studies evaluating the effectiveness of employer‐led interventions to prevent or reduce the adverse effects of substance use are lacking. Higher quality and mixed methods studies are needed to determine whether any of the interventions are generalizable and whether contextual adaptations are needed. In the meantime, there is a reason to believe that commonly recommended, employer‐led interventions may be effective in some environments.